PEMANFAATAN MOLYMOOD TERHADAP HASIL BELAJAR SISWA PADA KONSEP ALKANA, ALKENA DAN ALKUNA PADA SISWA KELAS X SMA NEGERI 2 DOLO - Sulhajir, Wahyuni; Nuryanti, Siti; Tangkas, I Made (Universitas Tadulako, 2013)
This research was done due to known that most students got difficulty in learning and understanding chemistry material particularly on alkana, alkena and alkuna concept. This problem occured because there was still any teacher who use conventional method in delivering the material. To make the material easy to learn, not boring and easy to understand, the teacher needs to give a learning media. The objective of this research was to increase the students’ learning outcome on the material of alkana, alkena and alkuna in SMA Negeri 2 Dolo by applying Mollymood aid. The population of the research was the tenth grade students of SMA Negeri 2 Dolo in academic year 2012/2013 with sample was 26 students of Class XA as the experimental class (given Mollymood aid for learning)and 26 students of Class XB as the control one (given conventional method). The technique of data collection done through instrument such as achievement test of alkana, alkena and alkuna. The data analysis result obtained average score on experimental class was 23.35 with deviation standard was 2.66 whereas for control class the average obtained was 20.73 with deviation standard was 2.77. Hypothesis testing result obtained tcounted = 4.59 and ttable 1.67 with significant level (α) = 0.05. Based on the research result, it showed that there was a significant difference between students’ learning outcome on chemistry taught using molymood aid and conventional one of the tenth grade students of SMA Negeri 2 Dolo in academic year 2012/2013.